Efektivitas edukasi anemia berbasis video animasi terhadap pengetahuan dan sikap remaja putri tentang tablet tambah darah - Desak Made Yulianti; Nancy Olii; Nurhidayah Nurhidayah; Veny Delvia Pombaile; Ni Made Dewi Anggraeni; Rina Sulisthia Arbie (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Iron deficiency anemia remains a prevalent health problem among adolescent girls and has adverse effects on quality of life and productivity. Health education delivered through engaging and easily accessible media, such as animated videos, has the potential to enhance understanding and foster positive attitudes toward the consumption of iron supplementation tablets. Purpose: To determine the effectiveness of animated video education on anemia on the level of knowledge and attitudes of young women about iron tablets. Method: This study employed a quasi-experimental design with a two-group pretest–posttest approach. The sample consisted of 80 adolescent girls, including 40 seventh-grade and 40 eighth-grade students, selected using an exhaustive sampling technique. Knowledge and attitudes were assessed before and after the intervention. Data were subsequently analyzed using the Wilcoxon and chi-square tests, with a significance level set at p < 0.05 Results: The anemia education delivered through animated videos significantly improved the knowledge and attitudes of adolescent girls in both grade groups (p=0.000). In addition, a significant difference was observed between seventh- and eighth-grade students after the intervention (p<0.05), with eighth-grade students exhibiting better outcomes. Conclusion: Animated video based anemia education was proven to be effective in improving the knowledge and attitudes of adolescent girls regarding iron supplementation tablets. Therefore, this medium can be recommended as a health promotion strategy to support anemia prevention efforts among adolescent girls. Keywords: Anemia; Animated Video; Attitude; Iron Supplementation; Knowledge. Pendahuluan: Anemia defisiensi besi masih menjadi permasalahan kesehatan yang banyak dijumpai pada remaja putri dan berdampak pada kualitas hidup serta produktivitas. Edukasi kesehatan melalui media yang menarik dan mudah diakses, seperti video animasi, berpotensi meningkatkan pemahaman dan membentuk sikap positif terhadap konsumsi tablet tambah darah. Tujuan: Untuk menganalisis efektivitas edukasi video animasi anemia terhadap tingkat pengetahuan dan sikap remaja putri tentang tablet tambah darah. Metode: Desain penelitian quasi-experimental dengan pendekatan two group pretest–posttest. Sampel berjumlah 80 remaja putri (40 siswi kelas 7 dan 40 siswi kelas 8) dipilih menggunakan teknik exhaustive sampling. Data diperoleh melalui penilaian tingkat pengetahuan dan sikap yang dilakukan sebelum dan setelah pemberian intervensi. Selanjutnya, di analisis menggunakan uji Wilcoxon dan chi-square pada tingkat signifikansi p < 0.05. Hasil: Edukasi video animasi anemia secara signifikan meningkatkan pengetahuan dan sikap remaja putri di kedua kelompok kelas (p=0>000). Selain itu, perbedaan signifikan juga ditemukan antara siswa kelas 7 dan 8 setelah intervensi (p<0.05), dengan performa yang lebih baik pada siswa kelas 7. Simpulan: Pemberian edukasi anemia melalui media video animasi terbukti efektif meningkatkan pengetahuan dan sikap remaja putri tentang tablet tambah darah. Kata Kunci: Anemia; Pengetahuan; Sikap; Tablet Tambah Darah; Video Animasi.